Hemoglobin Variability as Risk Factor of Left Ventricle Dilation in Chronic Kidney Disease Patient on Routine Hemodialysis - Iqbal Maulana; Hasanah Mumpuni; Irsad Andi Arso (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
Background: Several patients with chronic kidney disease (CKD) undergoing routine hemodialysis (HD) have abnormalities of left ventricle (LV) morphology with feature LV dilation due to volume overload and chronic ischemia, which has high risk of mayor adverse cardiovascular event. Anemia causes LV dilation through high output state mechanism. Anemia management in CKD patients causes hemoglobin (Hb) fluctuations or hemoglobin variability (Hb-Var) which is thought to cause LV dilation through relative repetitive ischemia mechanisms. Research linking Hb-Var as risk factor for LV dilation has never been done.Method: Matched case-control study was carried out by taking echocardiographic data of CKD patients undergoing routine HD in HD Unit Dr. Sardjito hospital. The LV diameter is divided into samples with LV (+) dilated profile as a case group, and LV (-) dilated as a control group. Matching was done on variables of age, gender and HD frequency. The HbVar parameter was calculated by the residual SD method based on the Hb value in the last 6 months. Fisher-Exact hypothesis test was used to assess the relationship between Hb-Var and LV dilation, while the logistic regression test was used for multivariate testing.Result: Total of 79 subjects entered in this study, there were 23 subjects of case groups and 28 subjects of control group after matching and adjusting the control formula. The proportion of high Hb-Var in the group with dilated LV (+) and dilated LV (-) were 21.7% and 17.9%, respectively. The Fisher-Exact test shows that there is no relationship between HbVar and LV dilation, with OR 1.28 (95% CI 0.32-5.10). Logistic regression test shows that there are no variables that affect independently of LV dilation.Summary: CKD patients undergoing routine HD with high Hb-Var profiles do not have a higher risk of LV dilation than patients with low Hb-Var profiles.